Analisis Pembakaran Ganda Bahan Bakar Natural Gas dan Biosolar pada Mesin Diesel Satu Silinder: Studi Efisiensi Termal dan Performa - Narantoko, Resi Aji; Riza, Abrar; Tanujaya, Harto (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2025)
This research discussion aims to determine the performance of the Jiandong 170F single-cylinder Diesel engine when operating on dual-fuel combustion, utilizing biodiesel as the primary fuel and natural gas. In this study, RCCI and low-temperature combustion (LTC) are methods of fuel mixing by using a mixture of B30 biodiesel fuel and natural gas. The characteristic of natural gas with a low cetane number causes the combustion process to occur at lower temperatures, resulting in early ignition of the upper dead point. This condition can be examined using the HCCI method. The test results showed a 4% increase in actual torque, worth 5.8 Nm, compared to the use of pure biodiesel. In addition, there is an increase in thermal efficiency of 5-10%, which is worth an average of 30%. This makes combustion more perfect, so that it contributes to a reduction in residual emissions or NOx.